In vitro bioassay methods for laboratory screening of novel mosquito repellents. Issue 4 (8th January 2014) - Deng, Wan; Zhu, Na; Mo, Jianchu
Abstract Repellents are highly effective in preventing humans from being bitten by mosquitoes and other blood‐feeding insects. Here we provide an overview of the representative in vitro bioassays for the laboratory testing of these agents. Currently, potential repellents are mostly evaluated on human skin, using the arm‐in‐cage method. However, for the testing of large numbers of chemicals for mosquito repellent activity, several in vitro bioassays have been established. Based on their components, as described in the recent literature, these can be categorized: (i) the natural tendency system; (ii) the membrane plus blood system; (iii) the skin plus attractants system; and (iv) the host plus netting system. The major advantages and disadvantages of these bioassays are discussed with the aim of establishing reliable and practical methods for discovering novel mosquito repellents.